Analysis of TikTok as a Social Media Platform and Its Effect on Elementary School Students’ Achievement - Deby Marta, Claudea; Kharisma, Inggria; Aisyah, Nurul; Azmi Alwi, Nur (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
This research is motivated by technological developments that have had a major impact on various aspects of life, including children and adolescents. TikTok is one of the social media platforms that provides diverse content in different contexts, which can lead to careless use. This platform is not only a source of entertainment but has also become an interactive space where children explore identity, share stories, and develop distinctive communication patterns. The purpose of this study is to examine the phenomenon of TikTok use in depth through a review of relevant literature discussing the relationship between social media, language pragmatics, and student learning achievement. This research employs the Systematic Literature Review (SLR) method. The data for this study were collected from various academic databases. The findings indicate that the pragmatic aspects of communication and the learning achievement of elementary school students are significantly affected, both positively and negatively. The use of TikTok by elementary school students as an interactive social media platform reflects communication patterns that are rich in pragmatic elements, particularly various types of speech acts.